Hubungan antara Mindfulness dengan Kecemasan akan Kematian pada Dewasa Madya - Rahmatul Hafidah; Zaujatul Amna; Dahlia Dahlia; Syarifah Faradina (Jurnal Ilmu Perilaku, 2023)
Death anxiety is an unpleasant emotional state that a person experiences when thinking about death. Anxiety can have a detrimental impact on mental health, especially in the middle adulthood stage, who experience death anxiety more often. One of the effective strategies to deal with death anxiety is to have mindfulness. The concept of mindfulness can help middle-aged adults to stay focused on doing and interpreting every activity or situation without thinking about abstract things, such as death. The purpose of this study was to investigate the relationship between mindfulness and death anxiety in middle adulthood. The total sample of 275 middle-aged adults was selected by accidental sampling technique. Data were collected using the Mindful Attention Awareness Scale (MAAS) and Death Anxiety Scale-Extended (DAS-Extended). The results of data analysis using the Spearman-Brown Formula showed that there was a negative relationship between mindfulness and death anxiety in middle adulthood. In other words, higher mindfulness will be associated with lower death anxiety, and vice versa. Therefore, mindfulness is associated with reduced death anxiety in middle adulthood. Keywords: Mindfulness, Death Anxiety, Middle Adulthood